تحسين أداء الشبكات الافتراضية الخاصة باستخدام تقنية التبديل متعدد الوسوم للبروتوكول - حجازية, محمد; يونس, معين (Latakia University Journal -Engineering Sciences Series, 2016)
بالرغم من كون الشبكات الافتراضية الخاصة تؤمن نقلاً آمناً وموثوقاً لبيانات الزبائن المشتركين في خدمتها إلا أنّ التشكيلات الأساسية المعتمدة عليها والمتمثلة بشبكات النقل غير المتزامن (ATM) Asynchronous Transfer Mode , وشبكات ترحيل الأطر Frame Relay, إلا أن الوصلات المعتمدة عليها هذه التقنيات تعتبر بطيئة نسبياً , وتسبب تأخيراً زمنياً. ومع النمو المتسارع لشبكة الانترنت و زيادة الحمل على الشبكة من حيث عدد المستخدمين ومزودات الخدمة. بدأت عملية البحث عن طرق توجيه فعالة وسريعة لرزم البيانات مع ضمان جودة الخدمة وتأمين إدارة وهندسة الحركة على الشبكة Traffic Engineering (TE). ظهرت تقنية التبديل متعدد الوسوم للبروتوكول Multi Protocol Label Switching ( MPLS) كتقنية معيارية حديثة تفي المتطلبات السابقة بعدما كانت في البداية طريقة لتحسين سرعة إرسال الموجهات .يقدم هذا البحث دراسة تحليلية عن تحسين أداء الشبكات الافتراضية الخاصة باستخدام تقنية التبديل متعدد الوسوم للبروتوكول Virtual Private Network-Multi Protocol Label Switching ( _VPN MPLS), عبر تحسين عمليات التوجيه على مستوى الطبقة الثالثة وتوفير زمن التأخير والتعقيد الناتج عن إعدادات بروتوكولات التوجيه على كامل الموجهات الداخلية في التقنية التقليدية, واقتصارها عل الموجهات الطرفية في شبكات MPLS_VPN. تم استخدام برنامج المحاكاة OPNET للحصول على النتائج التحليلية للتقنية الجديدة ومقارنتها مع التقنية القديمة.Although the fact that VPN provide a safe and reliable transfer of customers’ data, but the basic configurations on which they depend VPN and transport networks of asynchronous (ATM) and Frame Relay networks (FR).Link, that depend on them these techniques are relatively slow and cause a delay in time With the rapid growth of the Internet and increase the load on the network in terms of users and providers of service to look for ways of effective and fast routing packets of data while ensuring quality of service began(QoS)and class of service(Cos)and secure management and engineering movement(traffic) on the network and appeared the multi-switch tags of the Protocol(MPLS)standard modern technique verify the previous requirement safter she was initially way to improve the transmission speed routers. This paper presents an analytical study on improving the performance of virtual private networks using multi-protocol label switching( MPLS_VPN), by improving routing operations on the third level, minimizing the delays and complexity resulting from the routing on full internal routers in the traditional technical protocols settings and limited to Edge routers in networks MPLS_VPN. OPNET was used simulation software to get the results of the analysis and simulation of new technology and compare it with the old technology.